Impacts of Landscape Evolution on Heterotrophic Carbon Loss in Intensively Managed Landscapes - Yan, Qina; Kumar, Praveen (Frontiers in Water, 2021)
Soil respiration releases CO2 into the atmosphere that roughly balances the net primary productivity. It varies widely due to human disturbance on the land surface, particularly in intensively managed landscapes, including altering land cover, use of surface and sub-surface drainage tiles, and tillages. However, predictions of the spatial variability of soil respiration are facing great challenges due to a lack of understanding of the roles of accelerated soil erosion in agriculture fields. Here we simulate the soil respiration due to microbial decomposition of soil organic carbon (SOC), also called the heterotrophic carbon loss (HCL), by coupling soil transport, landscape evolution, redistribution of soil organic carbon on the land surface, soil moisture dynamics, and biogeochemical turnover in an agricultural field. The average HCL is higher in depositional areas than erosional areas, but it shows the highest spatial variance in areas that exhibit small soil depth change. It is the SOC redistribution, not the SOC stock or soil depth that directly controls HCL in a near-linear relationship. This work characterizes the roles of soil and SOC transport in restructuring the spatial variability of HCL at a high spatio-temporal resolution in a watershed.